Cholecystectomy does not worsen progression or outcomes in non-alcoholic fatty liver disease - Kakati, Donny; Kumar, Ujjwal; Russ, Kirk; Shoreibah, Mohamed; Kuo, Yong-Fang; Jackson, Bradford; Singal, Ashwani K. (Translational Gastroenterology and Hepatology; Vol 5 (January 2020): Translational Gastroenterology and Hepatology, 2019)
Background: Cholecystectomy is a frequently performed surgical procedure for symptomatic cholelithiasis, which is reported to be more common in patients with non-alcoholic steatohepatitis (NASH), given the common risk factors. However, the data remains unclear on the association of cholecystectomy with NASH. We performed a retrospective study to examine the association of cholecystectomy and NASH. Methods: Medical charts of patients with steatohepatitis related liver disease at a tertiary care center from 2004 to 2011 were stratified by cholecystectomy and defined by its history and/or absence of gallbladder on ultrasonography. Logistic regression model was built for predictors of cholecystectomy. Patients with NASH were stratified based on timing of cholecystectomy. The diagnosis of NASH and timing of cholecystectomy were compared based on baseline characteristics and outcomes (liver disease complications and survival) on follow up. Kaplan-Meier curves were generated for the two group comparisons. Chi-square and unpaired t-tests were used for comparing outcomes on follow up. P value